Developing a taxonomy of the built environment for disability studies. Methodological insights. - Stephanie Gamache; Yan Grenier; Patrick Fougeyrollas; Geoffrey Edwards; Mir Abolfazl Mostafavi (Journal of Accessibility and Design for All, 2017)
For a city to be inclusive, its physical environment needs to be identified, characterized and assessed prior to transformations and improvements. Such identification is the first step to impact on politics for citizens with impairments and functional limitations since environmental obstacles limits their social participation. The objective of this research was to develop a comprehensive and applicable information set for the description of the physical environment in support of the implementation of the United Nations Convention on the rights of persons with disabilities in Quebec City’s context. We developed a taxonomy based on the Human Development Model – Disability Creation Process (HDM-DCP). We reviewed documents containing nomenclatures with respect to the specific case of Quebec City’s physical environment. We organized the information under the original taxa of the HDM-DCP, this was carried out via an iterative process where elements of similar type were organized into a common level of one hierarchical branch under general categories. When categories linking objects to broader subcategories were not already identified, we expanded the structure by creating new sub-categories or hybrids. Applicability of the developed taxonomy was tested through field analyses and testing (photos of street sections) to determine whether it included all objects and infrastructures observed in the city. The resulting taxonomy was found to be useful in identifying/mapping elements of the physical environment. Both at the individual and collective level, it allows the identification of the elements that play a role in mobility, resulting in enhanced social participation or disabling situations for people with disabilities.